English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Can someone solve this equation: 2x (x-2) = 3 (x+10)

The answer is one of these:

27 and 2
-5/4 and 3
-2/3 and 6
-5/2 and 6
3 and 9

Thanks!

2006-11-25 07:30:47 · 5 answers · asked by irishmadmano6 1 in Science & Mathematics Mathematics

5 answers

2x(x - 2) = 3(x + 10)
2x² - 4x = 3x + 30
2x² - 7x - 30 = 0
(2x + 5)(x - 6) = 0
x = -5/2 or 6 ← option d

2006-11-25 07:37:43 · answer #1 · answered by Wal C 6 · 0 0

2x(x-2) = 3(x+10)
2x² - 4x = 3x + 30
2x² - 7x - 30 = 0
(2x + 5)(x - 6) = 0
x=-5/2 or 6

But you could have also figured it out just by plugging in the values to see which ones worked.

2006-11-25 15:41:01 · answer #2 · answered by Jim Burnell 6 · 0 0

2x^2-4x=3x+30
2x^2-7x-30
(x-6)(2x+5)
x= 6 and -5/2

2006-11-25 15:37:00 · answer #3 · answered by      7 · 0 0

You will find a full solution here:
http://users.vlo.gda.pl/~regulus/sol.png

Hope you can read my handwriting. Next time you will have an equation like that, remember, it's all about getting everything to one side of equation to have 0 on the other side and counting delta (b*b-4*a*c, where your equation is ax*x+bx+c) and then using it to count x
(x1=(-b-delta)/2a, x2=(-b+delta)/2a )

2006-11-25 16:57:41 · answer #4 · answered by enthernae 2 · 0 0

isnt it -6x squared??

2006-11-25 15:36:18 · answer #5 · answered by Nikki 2 · 0 0

fedest.com, questions and answers